2019
DOI: 10.1371/journal.pone.0226733
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach identifies Enhancer of Zeste Homolog 2 (EZH2) as a protective factor in epilepsy

Abstract: Complex neurological conditions can give rise to large scale transcriptomic changes that drive disease progression. It is likely that alterations in one or a few transcription factors or cofactors underlie these transcriptomic alterations. Identifying the driving transcription factors/cofactors is a non-trivial problem and a limiting step in the understanding of neurological disorders. Epilepsy has a prevalence of 1% and is the fourth most common neurological disorder. While a number of anti-seizure drugs exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…Possible homeostatic mechanisms after seizures have been proposed based on animal model systems of epilepsy. 14,15 One example comes from the work of Khan et al, 81 who found that enhancer of zeste homolog 2 (EZH2) was upregulated in mouse hippocampal neurons immediately after a bout of status epilepticus, during the latent period in which seizures are unlikely. EZH2 is a histone methylase important for regulating gene expression.…”
Section: Potential Mechanisms Of Homeostatic Plasticity In Epilepsymentioning
confidence: 99%
“…Possible homeostatic mechanisms after seizures have been proposed based on animal model systems of epilepsy. 14,15 One example comes from the work of Khan et al, 81 who found that enhancer of zeste homolog 2 (EZH2) was upregulated in mouse hippocampal neurons immediately after a bout of status epilepticus, during the latent period in which seizures are unlikely. EZH2 is a histone methylase important for regulating gene expression.…”
Section: Potential Mechanisms Of Homeostatic Plasticity In Epilepsymentioning
confidence: 99%
“…A limitation of this study is that the investigators used different hippocampi to extract protein and RNA. They validated their findings by WB, RT-qPCR, and LC-MS/MS [155].…”
Section: Multi-omics Integrationmentioning
confidence: 66%
“…A role in epileptogenesis of the EED interactor and H3K27me3 methylation co-regulator EZH2 is already evident by the occurrence of seizures in individuals with Weaver syndrome (Gibson et al, 2012;Kamien et al, 2018) and functionally by its ability to regulate differentially expressed genes across multiple rodent models of acquired epilepsy (Khan et al, 2019). Therefore, EED variants might also contribute to epileptogenesis, resulting in the occurrence of seizures as an infrequent aspect of Cohen-Gibson syndrome.…”
Section: Discussionmentioning
confidence: 99%